Expression of cytokines Th1 (IL-2, IL-12, IFN-γ, TNF-α), Th2 (IL-4, IL-10, TGF-β) and Th17 (IL-17) in circulating lymphocytes of guinea pigs inoculated with a field strain of Salmonella Typhimurium - Mejía, David (2020)
The aim of this study was to evaluate the relative expression of the cytokines involved in the immune response of Th1 (IL-2, IL-12, IFN-γ, TNF-α), Th2 (IL-4, IL-10 and TGF-β) and Th17 (IL-17) in 21 guinea pigs (Cavia porcellus) experimentally inoculated with a field isolate of Salmonella Typhimurium at a dose of 102 CFU/ml, intraperitoneally, and compared with a control group (inoculated with a thermally treated strain). Blood samples were taken on days 1, 3, 5, 7, 9, 15 and 30 post-inoculation (p.i.). Total RNA was extracted from lymphocyte cells and real-time RT-PCR was conducted using specific primers for each of the cytokines. The relative mRNA expressions were determined by the comparative method 2-ΔΔCt with respect to the calibrator (healthy guinea pig) and using GAPDH as a constitutive gene of reference as a normalizer. The expressions of the cytokine genes in the Treatment group showed an increase with respect to the Control group and an ascending kinetics throughout the study. In the first days there was a predominance of Th1 expressions over Th2, later both increased with a predominance of IL-4 and IL-17 from day 15 p.i. Inoculation of S. Typhimurium stimulated a major expression of IL-12 with respect to the other cytokines, which would induce a cellular or Th1 response in guinea pigs.